Cáncer y su asociación con patrones alimentarios en Córdoba (Argentina) - Pou, Sonia Alejandra (2014)
Introduction: Feeding habits play a prominent role in carcinogenesis. The dietary patterns approach applied to the study of chronic diseases is of increasing interest in nutritional epidemiology. Nevertheless, it has been seldom used in Latin America. Objective: To identify dietary patterns in adult population in Córdoba (Argentina) and to estimate their effects on the risk of colon-rectal (CRC), urothelial (UC), breast (BC) and prostate (PC) cancers. Methods: Four case control studies were conducted, 2006-2012 for CRC, PC, BC and UC. To identify the dietary patterns, a Principal Components Factor Analysis was conducted. A multilevel logistic regression was adjusted for the risk analyses. Results: Characteristic dietary patterns in the whole population, and in women and men independently, were identified. In the whole population South Cone and Sweet Beverages patterns behaved as promoters for CRC and UC while the Prudent Pattern had a protective effect. Female South Cone, Rural and Starchy patterns were associated to a higher BC risk. Prudent Pattern lowered BC risk. In men, South Cone, Sweet Beverages and Typical Measured patterns promoted PC. Conclusion: It is necessary to promote a regular intake of vegetables, fruits and diary products (although a moderate intake for men), and to reduce red meat (especially fat meat), processed meat, starchy vegetables, wine and sweet beverages intakes, to prevent the occurrence of cancer. In men, it is recommended a moderate intake of egg. In women, it is advised a moderate intake of refined grains, bakery products, oils and mayonnaise intake.